Cholesterol-Controlled Interaction of Ionic Liquids with Model Cellular Membranes - Hitaishi, Prashant (Langmuir : the ACS journal of surfaces and colloids, 2023)
While ionic liquids (ILs) are considered as prospective ingredients of new antimicrobial agents, it is important to understand the adverse effects of these molecules on human cells. Since cholesterol is the essential component of a human cell membrane, in the present study, the effect of an imidazolium-based IL has been investigated on the model membrane in the presence of cholesterol. The area per sphingomyelin lipid is found to reduce in the presence of the IL, which is quantified by the area-surface pressure isotherm of the lipid monolayer formed at the air-water interface. The effect is considerably diminished in the cholesterol-containing monolayer. Further, the IL is observed to decrease the rigidity of the cholesterol-free monolayer. Interestingly, the presence of cholesterol does not allow any change in this property of the layer at lower surface pressure. However, at a higher surface pressure, the IL increases the elasticity in the cholesterol-induced condensed phase of the lipid layer. The X-ray reflectivity measurement on a stack of cholesterol-free lipid bilayers proved the formation of IL-induced phase-separated domains in the matrix of a pure lipid phase. These domains are found to be formed by interdigitating the chains of the lipids, producing a thinner membrane. Such a phase is less intense in the cholesterol-containing membrane. All of these results indicate that the IL molecules may deform the cholesterol-free membrane of a bacterial cell, but the same may not be harmful to human beings as cholesterol could restrict the insertion in the cellular membrane of a human cell